Methods of Monitoring the Development and Spread of Harmful Organisms in Geese - Aminova Dildor Xolmurodovna (Scientific Trends, 2025)
In this article, in cases associated with a sharp increase in the volume of information in the planning and organization of alternative decisions on plant protection using information technologies in agricultural production, the speed of data processing, decision-making and their delivery to users and the development of harmful organisms in the field, and the spread of the disease.
Keywords: Cotton, harmfulness, monitoring, pheromone trap, microbiological, ecosystem, population, efficacy, phytosanitary, prevention, prognosis, harmfulness, ethnophages.